Flipped Classroom Model: Empowering Digital Literacy for Mathematics Learning in Society 5.0 - Yanuarto, Wanda Nugroho; Jaelani, Anton; Purwanto, Joko (Indonesian Journal of Science and Mathematics Education, 2021)
In the era of society 5.0, technology and education are likely two side of coin. Teachers can use technology in the classroom. Also, teachers play a role in maximizing the quality of learning. This study employed descriptive qualitative research. This study aimed produced an overview of flipped classroom used in learning activities, particularly in learning mathematics. The research data in this study were observations, semi-structure interviews, and documentation of flipped classroom learning activities. The research subjects were 37 seventh-grade students of one of junior high school in Purwokerto, Indonesia. The data analysis technique in this study consisted of four stages:1) data collection, 2) data reduction, 3) data presentation and 4) drawing conclusions. The results of this study are: 1) flipped classroom improves teachers and students digital literacy; 2) flipped classroom as one alternative learning model; 3) flipped classroom expressed students’ positive activities with technology; and 4) flipped classroom provide opportunities for parents interact with students in home activities.